2008
DOI: 10.1055/s-2008-1062723
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Cystic Fibrosis Patients According to the Glucose Tolerance

Abstract: Cystic fibrosis (CF) is associated with a long preclinical state of abnormal glucose tolerance. The aim of this study was (i) to evaluate the profile of glucose tolerance in young adults with CF and (ii) to compare these results with those obtained by a continuous subcutaneous glucose monitoring (CGMS). CF subjects with fasting glycemia inferior to 126 mg/dl were included in the study. An oral glucose tolerance test (OGTT) identified the subjects either with a normal glucose tolerance (NGT), or impaired glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…Similar to our findings, relative to an entirely paediatric cohort, adult CF subjects with NGT at OGTT have been shown to have diabetic glucose excursions at CGMS in 33-36% of the cases (11,13). Moreover, in selected high-risk adolescents with CF and NGT or IGT, pathological CGMS glucose excursions were reported in around 50-70% of the cases (10,12).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to our findings, relative to an entirely paediatric cohort, adult CF subjects with NGT at OGTT have been shown to have diabetic glucose excursions at CGMS in 33-36% of the cases (11,13). Moreover, in selected high-risk adolescents with CF and NGT or IGT, pathological CGMS glucose excursions were reported in around 50-70% of the cases (10,12).…”
Section: Discussionsupporting
confidence: 74%
“…There is now evidence that the OGTT method, evaluating fasting and 2-h postload glucose, may miss episodes of hyperglycaemia. It has been demonstrated recently that the continuous glucose monitoring system (CGMS) is a useful and valid tool in defining glucose metabolism in children and adults affected by CF with early glucose derangements (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies 174,[183][184][185][186][187][188][189]205 (one in German 174 ) provided sufficient data for 2 × 2 tables with actual numbers, not just per cent, so that CIs could be produced. Full details are given in the data extraction forms in Appendix 4.…”
Section: Resultsmentioning
confidence: 99%
“…Moreau et al, 187 from Strasbourg, compared the ROGTT with CGM in 49 patients. CGM involved 288 readings of tissue glucose per day.…”
Section: Moreau 2008mentioning
confidence: 99%
“…In one study of 22 CF subjects with NGT, a peak CGM glucose level of 182 mg/dL was identified, and observed post-prandial glucose peaks .200 mg/dL in one-third of CF subjects with NGT, half of IGT subjects, and all patients with CFRD. 80 Glucose excursions .200 mg/dL on CGM successfully predicted the development of IGT or CFRD as diagnosed by OGTT in a 2.5-year period. 81 Hameed 82 confirmed the validity and reproducibility of CGM in over 100 children with CF.…”
Section: Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%